Predictors of employee extra-role performance and turnover intentions in the public sector: an integrated model. (19th July 2006) - Albrecht, Simon
A model showing how six key organisational factors interrelate to influence Extra-Role Performance (ERP) and turnover intentions was tested. Confirmatory factor analysis showed that public sector survey respondents (n = 412) could reliably discriminate between measures of organisational justice, job autonomy, organisational support, trust in management, job satisfaction, affective commitment, ERP and turnover intentions. Furthermore, a structural equations model specifying procedural justice influencing trust in management, organisational support, job satisfaction and turnover intentions; job autonomy influencing job satisfaction and ERP; trust in management, organisational support and job satisfaction influencing affective commitment; and affective commitment influencing ERP and turnover intention provided a good fit to the data. Collectively the antecedent variables accounted for approximately 25% of the variance in ERP and 44% of the variance in turnover intentions. The results are discussed in terms of an integrated social exchange related theory of ERP and turnover intentions. Theoretical implications, practical implications, study limitations and future research possibilities are discussed.